PERBATASAN NEGARA DALAM PERSPEKTIF SOSIAL: Studi Perbatasan RI - Timor Leste - Cahyo Pamungkas (Jurnal Ledalero, 2016)
This article attempts to portray a picture of the cultural dimension in managing the boundaries of Nusa Tenggara Timur Province (NTT). The social dynamics of the culture of people at the boundary can be seen from the history of the formation of the boundaries, the dynamics of relationships between ethnic groups in districts adjacent to boundaries, and from social-cultural relationship problems that occur at boundaries. The conceptual framework used is that of a shift in the meaning of boundary from conventional social perspectives and approaches which emphasise the presence of a people’s and a state’s identity and control of the population, towards a post-modern approach which explains the appearance of globalizing agents at the boundary. Based on the results of interviews with a number of informants and a study of the literature, this study puts forward the proposition that the representation of the adat (customary law) community in the governing body of the state border is absolutely necessary to protect the basic rights of indigenous peoples who settled in the boundary area. Conventional border management, namely the traditional restriction of crossing boundaries, tend to put the state in violation of customary law that unites the two community cultures in colonial times.